Ujaran Kebencian di Media Sosial Perspektif Islam: Studi Takhrij dan Syarah Hadis - R. Muhammad Farhal Azkiya; Hidayatul Fikra; Erni Isnaeniah; M. Yusuf Wibisono (Gunung Djati Conference Series, 2022)
The very rapid development of IT and also in line with the flow of globalization that continues to soar makes the need for community IT to increase. Social media has also become a means for the community to establish social relations with each other, therefore it is not uncommon for friction between communities to occur, some blaspheme, justify, slander, spread hoaxes, and others. This study uses a qualitative approach that emphasizes literature study, in other words the researcher does not go directly to the field. This research also uses the takhrij and syarah methods on the hadith about hate speech through contemporary analysis. The result of the discussion is that hate speech is a speech that violates religious rules. Because hate speech can live without peace and madharat. Hate speech according to Islam includes backbiting, lying, namimah or provocation, and slander which are haraam and prohibited by Islam. And the principle that must be possessed in order to avoid hate speech behavior is to have faith in Allah, stay silent when angry or speak good things, Islam promotes peace and is moderate.